Managing an altered social context-Patients experiences of staying away from home while undergoing proton beam therapy - Marie‐Louise Möllerberg; Ulrica Langegård; Emma Ohlsson‐Nevo; Per Fransson; Birgitta Johansson; Karin Ahlberg; Katarina Sjövall (Wiley, 2020)
Abstract Aim To illuminate the experience of an altered social context for patients with primary brain tumours living away from home while undergoing proton beam therapy. Design A descriptive, qualitative cross‐sectional interview study. Methods Nineteen patients were interviewed between December 2015-August 2016, either during (N = 7) or before and after (N = 12) their proton beam therapy. A hermeneutical analysis was performed. Results Participants made adjustments to achieve control and well‐being during the treatment period. The analysis also revealed two interrelated patterns that helped participants adjust: being part of the family from a distance and seeking affinity. Conclusion It is important that patients receiving treatment far from home find a way to remain a part of their family and find affinity in the altered social context. Health professionals can prepare patients for the treatment period and can implement interventions to promote well‐being for both patients and their relatives.